1999
DOI: 10.1063/1.479097
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic and mesoscopic characterization of a bistable reaction system: CO oxidation on Pt(111) surface

Abstract: Influence of extended interactions on the surface dynamics in the catalytic CO oxidation on Pt single crystal substrateThe catalytic oxidation of CO by oxygen on a platinum ͑111͒ single-crystal surface in a gas-flow reactor follows the Langmuir-Hinshelwood reaction mechanism. It exhibits two macroscopic stable steady states ͑low reactivity: CO-covered surface; high reactivity: O-covered surface͒, as determined by mass spectrometry. Unlike other Pt and Pd surface orientations no temporal and spatiotemporal osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 49 publications
9
78
0
2
Order By: Relevance
“…In fact, evidence of such kind of transition has been reported in catalyzed reactions [8,9]. The occurrence of hysteretic effects around a first-order transition point has also been observed [10]. Very recently, we have performed a detailed study of the first-order IPT of the ZGB model presenting conclusive evidence of hysteretic effects [11].…”
Section: Introductionmentioning
confidence: 83%
“…In fact, evidence of such kind of transition has been reported in catalyzed reactions [8,9]. The occurrence of hysteretic effects around a first-order transition point has also been observed [10]. Very recently, we have performed a detailed study of the first-order IPT of the ZGB model presenting conclusive evidence of hysteretic effects [11].…”
Section: Introductionmentioning
confidence: 83%
“…These models exhibit many features characteristic of first-order IPT's that have also been found in numerous experiments, such as hysteretic effects [17,77] and abrupt changes of relevant properties when a control parameter is tuned around a coexistence point [17,18,19] (see also figure 2), etc. On view of these facts, special attention will be drawn to the discussion of first-order ITP's.…”
Section: Critical Behaviour Of Specific Reaction Systemsmentioning
confidence: 98%
“…For instance, it has been observed that oxygen and CO do not simply adsorb on random surface sites but rather they coalesce to form islands of CO and O species [58,85]. The actual reaction between CO and O is thought to take place at the edges of these islands.…”
Section: Carbon Monoxide Oxidationmentioning
confidence: 99%